2020
DOI: 10.1080/13621718.2020.1747764
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the residual stress distribution in repairs in H13 steel by friction hydro pillar processing

Abstract: The distribution of residual stresses (RS) in repairs generated by Friction Hydro-Pillar Processing (FHPP) in AISI H13 was investigated. Three axial force levels, with consequent different deposition rates, were applied to replicate possible repaired conditions. The contour (CM) and X-ray diffraction (XRD) methods were employed for RS analysis in samples that were also evaluated through metallography, microhardness analysis, micro-tensile and Charpy testing. CM produced 2D maps of the RS in the joints, showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Other authors revealed this same pattern, even with other materials or processes. Amavisca et al [18] noticed it when applying the counter method and the X-ray method in FHPP. Roy et al [37] and Yiet al [34] found it in all directions in the clad process.…”
Section: Residual Stress Evaluationmentioning
confidence: 98%
See 3 more Smart Citations
“…Other authors revealed this same pattern, even with other materials or processes. Amavisca et al [18] noticed it when applying the counter method and the X-ray method in FHPP. Roy et al [37] and Yiet al [34] found it in all directions in the clad process.…”
Section: Residual Stress Evaluationmentioning
confidence: 98%
“…Figure 8 presents the full width at half maximum (FWHM) of the neutron diffraction data for as-repaired conditions in the three directions and a hardness profile at 4 mm from the surface. As used by Yi et al [34] and Amavisca et al [18], the FWHM results were displayed with a relevant hardness curve to provide a better comprehension. Furthermore, as commented by Chen et al [35], hardness is a result of elasticity, plasticity, work hardening capability, mechanical strength, and toughness data, where angular diffraction is indicative of strain hardening, micro-strain, dislocation density, and grain refinement.…”
Section: Residual Stress Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Vicharapu et al [17] and Landell et al [18] reported the microstructure evolution and material flow of the taper holes damages repaired by friction hydro-pillar process. Amavisca et al [19] investigated the distribution of residual stresses generated by friction hydro-pillar repairing of AISI H13. In these methods, the tool head cannot transverse to achieve filling material and repairing the groove damage simultaneously.…”
Section: Introductionmentioning
confidence: 99%